Phytoaccumulation of heavy metals and protein expression by different vegetables collected from various parts of Khyber Pukhtunkhawa Province, Pakistan - Bakht, Jehan; Khan, Laleena; Shafi, Mohammad (Universiti Kebangsaan Malaysia, 2016)
The present study investigates heavy metal uptake and protein expression by different vegetables collected from various districts of Khyber Pakhtunkhawa province of Pakistan. Statistical analysis of the data showed that maximum concentration of Cd, Cr, Ni, Zn were found in radish and spinach, respectively, collected from Peshawar. Maximum Pb and Mg accumulation were found in cauliflower and pea at Swat followed by coriander at Haripur and minimum Pb uptake was noticed in radish taken from Nowshehra. Highest Cu uptake was detected in spinach at Nowshehra. Data regarding Cd, Cr, Pb, Cu, Ni, Mg and Zn concentration in water samples gathered from different sites of KPK indicated that maximum concentration of Cd was observed in Swat. Maximum Cr and Cu concentration were measured in water samples from Peshawar while maximum concentration of Pb and Ni were detected in water samples from Haripur. In case of soil samples, maximum Cd, Cr, Mg and Zn uptake was observed in soil sample at Nowshehra. Maximum Pb and Ni concentration was found in soil samples collected from Peshawar. Cu concentration was observed to be the highest in soil at Swat. Protein profile of different vegetables i.e. cauliflower, radish, carrot, turnip, pea, spinach, coriander and garlic sampled across five different sites showed that uptake of Cd, Cr, Pb, Cu, Ni, Mg and Zn by these vegetables caused the expression of numerous polypeptides.